The national consciousness of the translator and the reader’s emotions: the example of Henryk Sienkiewicz’s With Fire and Sword - Hryhorieva, Iryna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2017)
The article is devoted to the analysis of the novel With Fire and Sword by Henryk Sienkiewicz and of selected aspects of its translation into Ukrainian, Russian and English. Due to the fact that each translation can be seen as an independent work of art, the present material offers a chance to observe how the original can be interpreted by the translator who relies (or perhaps does not) on his or her cultural values and national consciousness. Emphasis has been put on the author’s and translators’ artistic techniques which influence the readers’ emotions. Attention has also been paid to how Polish cultural phenomena are expressed in the related (Ukrainian and Russian) and non-related (English) cultures. The problem of translators’ competence boundaries is considered as well.